Energy requirement and CO2 emissions of bioH2 production from microalgal biomass - Ferreira, Ana F. (2013)
This paper presents the life cycle inventory (LCI) of hydrogen production by Clostridium butyricum fermentation of Scenedesmus obliquus hydrolysate. The main purpose of this work was to evaluate the potential of H2 production from microalgal biomass and the respective energy consumption and CO2 emissions in the bioconversion process considering the microalga production, acid hydrolysis of S. obliquus biomass, preparation of the inoculum and culture media, and fermentation. The scale-up to industrial production was not envisaged. The hydrogen yield obtained in this work was 2.9 ± 0.3 mol H2/mol sugars in S. obliquus hydrolysate. Results show that this process of biological production of hydrogen can achieve 7270 MJ/MJH2 of energy consumption and 670Kg CO2/MJH2. The microalgal culture is the stage responsible for 98% of these total final values due to the use of artificial lighting. All stages and processes with the highest values of energy consumption and CO2 emissions were identified for future energetic and environmental optimisation.